2015
DOI: 10.1093/database/bav077
|View full text |Cite
|
Sign up to set email alerts
|

MetazSecKB: the human and animal secretome and subcellular proteome knowledgebase

Abstract: The subcellular location of a protein is a key factor in determining the molecular function of the protein in an organism. MetazSecKB is a secretome and subcellular proteome knowledgebase specifically designed for metazoan, i.e. human and animals. The protein sequence data, consisting of over 4 million entries with 121 species having a complete proteome, were retrieved from UniProtKB. Protein subcellular locations including secreted and 15 other subcellular locations were assigned based on either curated exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 44 publications
0
63
0
Order By: Relevance
“…To identify transcripts encoding secreted proteins, we used the MetazSecKB knowledgebase [30]. MetazSecKB identifies secretory proteins based on either curated evidence of secretion (annotated and reviewed in the UniProtKB/Swiss-Prot dataset) or being “highly likely” to be secreted based on computationally predicted secretory protein sequences, without containing transmembrane domains or endoplasmic reticulum (ER) retention signals, by several tools (SignalP4, Phobius, TargetP and WoLF PSORT).…”
Section: Methodsmentioning
confidence: 99%
“…To identify transcripts encoding secreted proteins, we used the MetazSecKB knowledgebase [30]. MetazSecKB identifies secretory proteins based on either curated evidence of secretion (annotated and reviewed in the UniProtKB/Swiss-Prot dataset) or being “highly likely” to be secreted based on computationally predicted secretory protein sequences, without containing transmembrane domains or endoplasmic reticulum (ER) retention signals, by several tools (SignalP4, Phobius, TargetP and WoLF PSORT).…”
Section: Methodsmentioning
confidence: 99%
“…To predict the A. catenella secretome, we applied bioinformatics tools to the total proteome obtained from the A. catenella transcriptome (Zhang et al ., ). This secretome contains 2 779 proteins depicting 2.4% of the total proteome, which is similar to the proportions reported for: (i) the brown algae Ectocarpus siliculosus (3.4%) (Terauchi et al ., ), (ii) the plant pathogenic fungus Fusarium graminearum (4.2%) (Brown et al ., ), (iii) a nematode (9.2%) (Gahoi and Gautam, ) and (iv) human/animals (8.1%) (Meinken et al ., ). This similarity shows that generally < 10% of the total proteins are secreted, regardless of the eukaryotic kingdom considered.…”
Section: Discussionmentioning
confidence: 99%
“…Table 11). We therefore intersected this group of genes with curated and highly-likely predicted secreted proteins from the MetazSecKB database (Meinken, Walker, Cooper, & Min, 2015) and found that secreted proteins were highly enriched (59 of the 236 common genes (25%), p<0.0001). We subdivided these genes into those with concordant or discordant regulation between CPT treatment and Irf4 -/-(Supp .…”
Section: Irf4 Mediates Camp-promoted Transcriptional Eventsmentioning
confidence: 99%